2023
DOI: 10.1186/s40168-023-01460-x
|View full text |Cite
|
Sign up to set email alerts
|

Sputum bacterial load and bacterial composition correlate with lung function and are altered by long-term azithromycin treatment in children with HIV-associated chronic lung disease

Abstract: Background Long-term azithromycin (AZM) treatment reduces the frequency of acute respiratory exacerbation in children and adolescents with HIV-associated chronic lung disease (HCLD). However, the impact of this treatment on the respiratory bacteriome is unknown. Method African children with HCLD (defined as forced expiratory volume in 1 s z-score (FEV1z) less than − 1.0 with no reversibility) were enrolled in a placebo-controlled trial of once-week… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Baseline bacterial communities mainly consisted of non-traditional bacteria (anaerobes and bacteria typically classified as oral commensals), despite the enrollment criteria of a positive PA culture. Recent microbiome studies in children have reported similar non-traditional bacteria in cohorts that include sputum from children with HIV [ 21 ], in an asthma study that collected hypopharyngeal aspirates [ 22 ] and other studies from early PA infection in CF [ 23 ]. Sputum from adults with CF collected prior to AZ treatment was more typically dominated by traditional CF pathogens, however a few subjects did exhibit less dominated bacterial communities that included anaerobes, similar to what we observed [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Baseline bacterial communities mainly consisted of non-traditional bacteria (anaerobes and bacteria typically classified as oral commensals), despite the enrollment criteria of a positive PA culture. Recent microbiome studies in children have reported similar non-traditional bacteria in cohorts that include sputum from children with HIV [ 21 ], in an asthma study that collected hypopharyngeal aspirates [ 22 ] and other studies from early PA infection in CF [ 23 ]. Sputum from adults with CF collected prior to AZ treatment was more typically dominated by traditional CF pathogens, however a few subjects did exhibit less dominated bacterial communities that included anaerobes, similar to what we observed [ 18 ].…”
Section: Discussionmentioning
confidence: 99%